Cervical Cancer Prevention and Screening - Ming Tsai; Caroline Pessel; Molly Cason; Erin Fitzgerald; Amisha Shah; So-Young Oh; Sabrina Lee; Violetta Kraja; Dorice Vieira; Julio Garcia; Elizabeth Maxwell; Scarlett Phan (Association of American Medical Colleges, 2011)
Abstract Introduction The complexity of the human papilloma virus (HPV)-host interaction, along with dense cervical cancer screening guidelines, hampers students' easy learning of the subject. This online learning module intends to provide a comprehensive overview of HPV infection to help students better understand the rationale behind the screening protocol. The content of this module summarizes key concepts such as viral structure and replication, human immune-defense, immunization strategy, pathogenesis of cervical pre-cancer and cancer, and finally, prevention and management strategy of HPV infection in gynecologic patients. The target audience will be primarily third-year medical students rotating through their OB-GYN clerkship. Methods The module takes advantage of the audio-visual effects to maximize student learning. It is organized in sessions of subtopics with core text, embedded images, illustrations, and recorded voice-over script. In addition, there is a video at the end of the module which simulates a patient encounter in a doctor's office to discuss cervical cancer screening and management. Pre- and posttest questions help the viewer keep track of their progress upon completion. Results Since making the online module active in November 2009, we have collected 19 evaluations from third-year OB-GYN clerkship medical students who have completed the module. The evaluation measures the module's effectiveness to the participant's learning. Of the 19 evaluations, 61% said the module matched very well or well to their learning needs, 24% said that it matched satisfactorily to their needs, and 15% said that the module didn't match at all to their learning needs. Of the 19 evaluations, 78% said the module was extremely clear, 10% said it was not at all clear, 42% said the module was an extremely effective way to teach the subject, and 10% said it was not at all an effective way. Discussion Based on the comments, this probably is a reflection of well-taught concepts on viral structure and immunology during the first and second year of the students' curriculum. However, it was not our intention to present an in-depth review of immunology but rather to present a brief introduction to help students better understand the clinical implication of HPV infection.